Land Use Affects Carbon Sources to the Pelagic Food Web in a Small Boreal Lake. - Päivi Rinta; Maarten van Hardenbroek; Roger I Jones; Paula Kankaala; Fabian Rey; Sönke Szidat; Matthew J Wooller; Oliver Heiri (PLoS ONE)
Small humic forest lakes often have high contributions of methane-derived carbon in their food webs but little is known about the temporal stability of this carbon pathway and how it responds to environmental changes on longer time scales. We reconstructed past variations in the contribution of methanogenic carbon in the pelagic food web of a small boreal lake in Finland by analyzing the stable carbon isotopic composition (δ13C values) of chitinous fossils of planktivorous invertebrates in sediments from the lake. The δ13C values of zooplankton remains show several marked shifts (approx. 10 ‰), consistent with changes in the proportional contribution of carbon from methane-oxidizing bacteria in zooplankton diets. The results indicate that the lake only recently (1950s) obtained its present state with a high contribution of methanogenic carbon to the pelagic food web. A comparison with historical and palaeobotanical evidence indicates that this most recent shift coincided with agricultural land-use changes and forestation of the lake catchment and implies that earlier shifts may also have been related to changes in forest and land use. Our study demonstrates the sensitivity of the carbon cycle in small forest lakes to external forcing and that the effects of past changes in local land use on lacustrine carbon cycling have to be taken into account when defining environmental and ecological reference conditions in boreal headwater lakes.